Analysis needed for action plan re project entitled strengthening/building national accreditation bodies - London, Ethley ([s.n.] [S.l.], 1999)
Makes recommendations for the establishment of national accreditation bodies in Guyana, Barbados and Suriname. Presents action plans for each of these territories.